Urea Unfolding Study of E. coli Alanyl-tRNA Synthetase and Its Monomeric Variants Proves the Role of C-Terminal Domain in Stability. (4th November 2015) - Banerjee, Baisakhi; Banerjee, Rajat
Abstract : E. coli alanyl-tRNA exists as a dimer in its native form and the C-terminal coiled-coil part plays an important role in the dimerization process. The truncated N-terminal containing the first 700 amino acids (1–700) forms a monomeric variant possessing similar aminoacylation activity like wild type. A point mutation in the C-terminal domain (G674D) also produces a monomeric variant with a fivefold reduced aminoacylation activity compared to the wild type enzyme. Urea induced denaturation of these monomeric mutants along with another alaRS variant (N461 alaRS) was studied together with the full-length enzyme using various spectroscopic techniques such as intrinsic tryptophan fluorescence, 1-anilino-8-naphthalene-sulfonic acid binding, near- and far-UV circular dichroism, and analytical ultracentrifugation. Aminoacylation activity assay after refolding from denatured state revealed that the monomeric mutants studied here were unable to regain their activity, whereas the dimeric full-length alaRS gets back similar activity as the native enzyme. This study indicates that dimerization is one of the key regulatory factors that is important in the proper folding and stability of E. coli alaRS.